Mechanism of Lithium Diisopropylamide-Mediated Substitution of 2,6-Difluoropyridine - Viciu, Mihai S. (2010)
Treatment of 2,6-difluoropyridine with lithium diisopropylamide in THF solution at −78 °C effects ortholithiation quantitatively. Warming the solution to 0 °C converts the aryllithium to 2-fluoro-6-(diisopropylamino)pyridine. Rate studies reveal evidence of a reversal of the ortholithiation and a subsequent 1,2-addition via two monomer-based pathways of stoichiometries [ArH•i-Pr(2)NLi(THF)](‡) and [ArH•i-Pr(2)NLi(THF)(3)](‡). Computational studies fill in the structural details and provide evidence of a direct substitution without the intermediacy of Meisenheimer complex.